On the determinants of capital costs in Brazil's manufacturing industries - Kálmán Dezséri (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1990)
The Brazilian economy has undergone profound changes since the early 1970s. During this time, the external and internal economic conditions significantly altered. The two oil shocks, changes of the interest rates on the international capital markets, the following debt crisis, terms of trade deterioration, soaring inflation rate, high external and public deficits are the uppermost phenomena which characterised the Brazilian economy. From the point of view of economic policy, it is very important that the stabilisation programs should be accompanied by a successful structural adjustment process. New investments financed from domestic and/or foreign sources have definite significance in the realisation of such goals. Under these prevailing conditions the clear-cut answer to, and the knowledge of the main determinants of the social and private cost of capital are necessary and sine qua non to a more efficient utilisation of this production factor.
Keywords: 330; Kapitalkosten; Industrie; Investition; Kredit; Brasilien